Penerapan Terapi Madu terhadap Penyembuhan Luka pada Pasien Ulkus Dekubitus di RSUD Kabupaten Tangerang - Astika Nisa Putri; Imas Sartika; Nurfadila Nurfadila (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Background: According to the National Pressure Ulcer Advisory Panel, a decubitus wound is an area of ??scar tissue on the skin or soft tissue that covers a protruding bone. Wound treatment from various traditional medical sciences such as Ayurveda, traditional Chinese medicine, or traditional Roman medicine, one of which uses honey as a wound treatment modality. Research Objective: To determine nursing care for decubitus ulcer patients using honey therapy intervention for wound healing. Research Results: The results of the first day of implementation were that wounds that were previously open became closed. The results of the second day of implementation were that granulation tissue began to appear. And the results of the implementation on the third day were a reduction in the area of ??the wound from 4x3 cm to 3x3 cm. Conclusion: Based on the results of implementation and evaluation for 3 days with the intervention of providing honey therapy for wound healing. Honey therapy intervention for wound healing carried out in a multidisciplinary manner produces significant changes both objectively and subjectively. Suggestion: It is hoped that honey therapy can become an independent nursing action in healing wounds.